METHODOLOGY OF LABELING DENDRITIC CELLS IN THE COLONIC MUCOSA IN EXPERIMENTAL ULCERATIVE COLITIS - Правоторова О. С.; Сілкіна Ю. В. (World of Medicine and Biology, 2014)
There is a problem - labeling of immune cells with monoclonal antibodies to CD-receptors because appears the cross expression of cell determinants by several types of leukocytes, that requires to use of two or three markers for identification some cell clusters. No exception the dendritic cells that have identical antigenic tags the same the histiocytes, B-lymphocytes. The aim - to find a specific marker of dendritic cells within the inflamed mucosa of the colon in experimental ulcerative colitis. We were studied colon laboratory Wistar rats, which modeled ulcerative colitis by administering trinitrobenzolsulfonic acid in the colon. It was found that the most important marker of dendritic cells in the mucosal part of the colon is S-100 because accumulates in the cytoplasm dendritic cells, but not leukocytes and histiocytes, not requires differentiation with neural elements. Marker allows to investigate the details of the heterogeneity of its accumulation in the cytoplasm of dendritic cells.